Weed management using tillage, seed rate and bed planting in durum wheat (Triticum durum Desf.) under an organic agriculture system. Issue 14 (6th December 2022) - Hasam, Hasamuddin; Kaur, Simerjeet; Kaur, Harinderjeet; Kaur, Navjyot; Kaur, Tarundeep; Aulakh, Charanjit S; Bhullar, Makhan S
ABSTRACT: Weed management is a major obstacle in conversion from conventional to organic agriculture system, and objective of this study was to manage weeds in organically grown durum wheat. The treatment combinations of conventional tillage (CT) or deep tillage (DT) with 50% higher plant densities, zero tillage (ZT) with and without residues, straw mulching 6 t ha −1 and bed planting plus 25% higher plant density followed by hand pulling were evaluated for weed control in durum wheat in a two-year study. Tillage has differential effect on weed seed distribution and more than 60% of weed seeds were concentrated in 0–7.5 cm soil layer in CT and ZT, whereas 50.9% of weed seeds were displaced to 15–30 cm soil layer in DT. Bed planting plus 25% higher plant density followed by hand pulling resulted in lowering of weed density and biomass by 61.2% and 58.9%, respectively, at harvest. The maximum growth parameters, yield attributes and wheat grain yield, were obtained under bed planting with 25% higher plant density and one hand pulling. Sowing of durum wheat on raised beds or ZT with residue retention may be used as an effective and economical weed management tool under organic agriculture systems.